Integrated Hepatitis C Testing and Linkage to Care at a Local Health Department Sexually Transmitted Disease Clinic: Determining Essential Resources and Evaluating Outcomes. Issue 4 (April 2018) - Rhea, Sarah; Seña, Arlene C.; Hilton, Alison; Hurt, Christopher B.; Wohl, David; Fleischauer, Aaron
Abstract : Abstract: Guidance about integration of comprehensive hepatitis C virus (HCV)-related services in sexually transmitted disease (STD) clinics is limited. We evaluated a federally funded HCV testing and linkage-to-care program at an STD clinic in Durham County, North Carolina. During December 10, 2012, to March 31, 2015, the program tested 733 patients for HCV who reported 1 or more HCV risk factor; 81 (11%) were HCV-infected (ie, HCV antibody-positive and HCV ribonucleic acid-positive). Fifty-one infected patients (63%) were linked to care. We concluded that essential program resources include reflex HCV ribonucleic acid testing; a dedicated bridge counselor to provide test results, health education, and linkage-to-care assistance; and referral relationships for local HCV management and treatment. Abstract : Hepatitis C virus (HCV) testing and linkage-to-care programs at local health department sexually transmitted disease clinics should consider prioritizing the following resources: reflex HCV ribonucleic acid testing, a dedicated HCV bridge counselor, and referral relationships for local HCV management and treatment.Supplemental digital content is available in the text.